2018
DOI: 10.1039/c8dt01717d
|View full text |Cite
|
Sign up to set email alerts
|

Interception of intermediates in phosphine oxidation by mesityl nitrile-N-oxide using frustrated Lewis pairs

Abstract: Phosphine oxidation by MesCNO is rapid; however, an FLP strategy intercepts the 1,3 addition products including [MesC(R3P)NOB(C6F5)3] (R = Ph 1, p-tol 2), [MesC(Mes2PH)NOB(C6F5)3] 3 (MesC(NOB(C6F5)3)Ph2P)2(CH2)n (n = 2: 4, 3: 5) and [MesC(Ph3P)NOB(C6F4H)3] 6. These species are shown to react with tBuOK or [Bu4N]F permitting the oxidation to proceed via a process involving borane dissociation. Similarly, the equilibrium established by 1 with B(C6F4H)3 and 6 with B(C6F5)3 provides experimental support for the "C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…152 Further investigation into the B(2,3,5,6-F4C6H)3/PPh3 FLP found it could trap out the 1,3-addition product upon addition of mesityl isocyanate (Scheme 24, bottom). 153 This gave evidence towards the Cummins proposition, which suggested that the oxidation of phosphines by mesitylisocyanate occurred through the initial interaction between the carbon atom of the isocyanate and the phosphine. 154 Scheme 24: Activation of N2O and mesityl isocyanate by FLP containing B(2,3,5,6-F4C6H)3 as the Lewis acidic component.…”
Section: Further Small Molecule Activation By Flpsmentioning
confidence: 92%
See 1 more Smart Citation
“…152 Further investigation into the B(2,3,5,6-F4C6H)3/PPh3 FLP found it could trap out the 1,3-addition product upon addition of mesityl isocyanate (Scheme 24, bottom). 153 This gave evidence towards the Cummins proposition, which suggested that the oxidation of phosphines by mesitylisocyanate occurred through the initial interaction between the carbon atom of the isocyanate and the phosphine. 154 Scheme 24: Activation of N2O and mesityl isocyanate by FLP containing B(2,3,5,6-F4C6H)3 as the Lewis acidic component.…”
Section: Further Small Molecule Activation By Flpsmentioning
confidence: 92%
“…154 Scheme 24: Activation of N2O and mesityl isocyanate by FLP containing B(2,3,5,6-F4C6H)3 as the Lewis acidic component. 150,153 Figure 7: Proposed mechanism for autoinduced FLP hydrogenation of imines. 155…”
Section: Further Small Molecule Activation By Flpsmentioning
confidence: 99%
“…Nonetheless, FLP chemistry also provides an avenue for intervening in reactions and trapping species thought to be intermediates. [62][63][64] Alternatively, impact from the concept of FLPs could arise from applications in which FLPs and transition-metal catalysts are used in tandem. 65 Another possibility is the use of FLPs to generate new materials derived from complementary polymers.…”
mentioning
confidence: 99%
“…[18e,2 0] We envisioned ap rocess wherein an itrile oxide would first be generated in situ from dehydrochlorination of oxime chlorides,w hich are readily prepared. [21] The1,3-dipole of nitrile oxide would then attack the electrophilic boron atom of arylboronic acids, resulting in ab oron ate complex, [22] which might undergo as tereospecific 1,4-metalate shift forming ketoxime boronic acid complex. Subsequent hydrolysis of the ketoxime boronic acid complex removes the boron acid part and highly stereoselective ketoxime products might result ( Figure 1C).…”
mentioning
confidence: 99%